Pentingnya Analisis Jabatan Dalam Meningkatkan Kompetensi Organisasi - Wafiq Fathurrohman; Muhammad Saiful Bahri; Dwi Ratnasari; Mariyatul Kiptiyah; Mu’alimin (CV. ITTC INDONESIA, 2024)
Job analysis has an important role in an organization, especially in overcoming the problem of declining employee performance due to declining organizational competence. So, job analysis plays an important role in improving organizational competence. This research aims to find out how important job analysis is in improving organizational competence. The method used is a literature review study. Literature review studies can be taken from various reference sources such as journal articles and books. The literature review is useful for developing a theoretical and research framework and can provide insight into the importance of job analysis in improving organizational competence.